14 Long-term Efficacy of Brexpiprazole in Patients with Schizophrenia with Clinically Relevant Levels of Negative Symptoms. (12th March 2019) - Weiss, Catherine; Zhang, Peter; Baker, Ross A; Hobart, Mary; Hefting, Nanco; Meehan, Stine R
Abstract: Background: Effective treatments for patients with high levels of negative symptoms of schizophrenia are lacking. Brexpiprazole is a serotonin–dopamine activity modulator that is a partial agonist at 5-HT1A and dopamine D2 receptors, and an antagonist at 5-HT2A and noradrenaline alpha1B/2C receptors, all with subnanomolar potency. Long-term treatment with brexpiprazole demonstrated broad efficacy across all five Marder factor groupings, including positive, negative, disorganized thoughts, uncontrolled hostility/excitement, and anxiety/depression. This post-hoc analysis of long-term effects of brexpiprazole in patients with clinically relevant levels of negative symptoms of schizophrenia is based on data from two similarly designed short-term, placebo-controlled studies (Vector; NCT01396421 or Beacon; NCT01393613) for the brexpiprazole-treated patients who continued into an open-label extension study (Zenith; NCT01397786). Methods: In the short-term studies, patients with acute schizophrenia were randomly assigned to fixed once-daily doses of brexpiprazole 0.25mg (Vector), 1mg (Beacon), 2mg, 4mg or placebo for 6weeks. The long-term study was an open-label, 52-week (amended to 26weeks), safety extension study with flexible-dose (1–4mg/day) brexpiprazole. The post-hoc analyses were performed on brexpiprazole-treated patients from the short-term studies who continued into the long-term study, and who had clinically relevant negative symptoms, defined as PANSS Factor Score for Negative Symptoms (PANSS-FSNS; N1, N2, N3, N4, G7, G16) of ≥24, and score of ≥4 on at least two of three core negative symptom PANSS items at randomization in the parent study. The outcome of the analysis included change from baseline to up to 58weeks in PANSS-FSNS, PANSS Total, and PSP. Safety was also assessed. Results: A total of 187 patients with clinically relevant levels of negative symptoms in the parent study rolled-over into the open-label extension study and were available for analysis. Eighty-three of these patients remained in the studies for 58weeks. Due to the study amendment, not all patients had the opportunity of complete 52weeks of open-label treatment. Baseline PANSS Total score was 104.4, while baseline PANSS-FSNS was 27.6 and baseline PSP Total score was 41.3. Mean change (SD) from baseline in PANSS-FSNS was –10.9 (5.0), and –44.2 (17.5) for PANSS Total score at Week 58. Change from baseline (SD) to Week 58 for PSP Total score was 24.8 (12.9) with improvement in all domains (socially useful activities, personal and social relationship, self-care, and disturbing and aggressive behaviors). The TEAEs reported ≥5% were schizophrenia (18.9%), insomnia (8.6%), weight increased (5.9%) and akathisia (5.9%). Conclusion: This post-hoc analysis suggests that brexpiprazole has long-term effectiveness on negative symptoms and functioning in patients with schizophrenia and clinically relevant levels of negative symptoms. Funding Acknowledgements: The study was funded by Otsuka Pharmaceutical Development & Commercialization Inc. and H. Lundbeck A/S